Analysis of Athletic performance, psychology and athletic satisfaction for sport and life in China - Yang Liu; Weifang Hai (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The main objective of the study is to determine the connection between athletic performance, psychology, and athlete satisfaction level in athletes attending physical education institutions in China. In doing so, the study aims to analyse the differences between their level of self-satisfaction by psychoanalytical compartmentalization of burnout and ego resilience. Data is collected from a targeted population of individual respondents i.e., different athletes attending Chinese physical education high schools. A survey questionnaire technique has been used as the primary instrument of data collection with target respondents selected using a random sampling technique. Moreover, to analyse the data, PLS-SEM technique has been used in the study. The findings of the study illustrate that high levels of stress have a considerably adverse effect on the performance of athletes, leading to lower levels of self-esteem and work satisfaction. Furthermore, the mediating role of burnout of athlete’s performances vis-à-vis stress and athlete’s ability to handle stress is also explored. Finally, a comparative study of the high ego resilience group with low ego resilience group has been performed concluding in the favour of the former group which reports a higher level of athlete satisfaction in response to performance.